2021
DOI: 10.1037/rep0000366
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of medical comorbidities to psychological health at 2 and 5 years following traumatic brain injury (TBI).

Abstract: Results are consistent with previous studies demonstrating the high prevalence of medical comorbidities following traumatic brain injury and extend these findings to veterans and service members. This study suggests that medical comorbidities may have a cumulative impact on poor psychological health after traumatic brain injury. Rehabilitation professionals and other treatment providers should screen for and treat medical conditions as part of a synergistic approach to post-TBI care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…3 and 4 ). Together, these results suggest that patterns in the health status transition of patients with TBI emerge along the course of their comorbidity, which is consistent with previous reports 45 , 47 – 51 .…”
Section: Discussionsupporting
confidence: 92%
“…3 and 4 ). Together, these results suggest that patterns in the health status transition of patients with TBI emerge along the course of their comorbidity, which is consistent with previous reports 45 , 47 – 51 .…”
Section: Discussionsupporting
confidence: 92%
“…Together, these results suggest that attention to the health status transition patterns in TBI emerge along with the projection of comorbidity, which is consistent with previous reports [47][48][49][50][51][52] .…”
Section: Discussionsupporting
confidence: 92%
“…Using a medical comorbidities interview adapted from the National Health and Nutrition Examination Survey (NHANES),37 respondents were asked whether a doctor or other healthcare provider had ever diagnosed them with a health condition (ie, chronic pain; fractures to hip, wrist, or spine; hypertension; sleep apnea; sexual dysfunction; respiratory illness; high blood cholesterol; osteoarthritis; cataracts; diabetes; stroke; cancer; liver disease; kidney stones; myocardial infarction; rheumatoid arthritis; other health conditions; other thyroid disease). These 18 medical comorbidities have demonstrated significant associations to meaningful rehabilitation outcomes within the VA TBIMS national database 38. For the current study, the numbers of health conditions reported were summed into a total comorbidity burden variable.…”
Section: Methodsmentioning
confidence: 99%
“…These 18 medical comorbidities have demonstrated significant associations to meaningful rehabilitation outcomes within the VA TBIMS national database. 38 For the current study, the numbers of health conditions reported were summed into a total comorbidity burden variable. In addition, utilization of mental health services within the year prior to the follow-up assessment was coded as follows: yes = 1; no = 0.…”
Section: Smv Injury-related Informationmentioning
confidence: 99%